PENDAMPINGAN DAN SOSIALISASI SITUS BELAJAR SEBAGAI PENUNJANG PEMBELAJARAN ONLINE - Nurul Fatehah; Teddy Dyatmika (As-Sidanah, 2021)
The COVID-19 pandemic has had a profound impact on all areas of life, including education. The education system, which was originally face-to-face, had to be replaced with online learning. Various problems arise related to the implementation of the Distance Learning or PJJ system. This system makes parents have to participate more in supervising as well as being a substitute for teachers at home in the learning process of their children. In addition, homeschooling also raises problems where students find it difficult to understand the material given by the teacher. The decrease in enthusiasm for learning becomes a problem when the PJJ system seems monotonous and boring. To support the government's program in breaking the chain of the spread of COVID-19 without reducing the effectiveness of online learning implemented by the Ministry of Education and Culture, this activity was carried out. This activity is expected to help reduce the anxiety of parents who are afraid that their children are not serious and have difficulty in learning. In addition, it is hoped that this activity will help participants to easily understand the material that has not been mastered. The methods of socialization, demonstration, and mentoring are carried out directly. The success of this activity can be seen from the assistance of the participants in solving the problems faced and the enthusiasm of the participants during the activity.